A palladium-catalyzed approach to allenic aromatic ethers and first total synthesis of terricollene A. Issue 27 (17th June 2021) - Huang, Chaofan; Shi, Fuchun; Cui, Yifan; Li, Can; Lin, Jie; Liu, Qi; Qin, Anni; Wang, Huanan; Wu, Guolin; Wu, Penglin; Xiao, Junzhe; Xu, Haibo; et al.
Abstract : A palladium-catalyzed C–O bond formation reaction between phenols and allenylic carbonates to give 2, 3-allenic aromatic ethers with decent to excellent yields under mild reaction conditions has been described. Abstract : A palladium-catalyzed C–O bond formation reaction between phenols and allenylic carbonates to give 2, 3-allenic aromatic ethers with decent to excellent yields under mild reaction conditions has been described. A variety of synthetically useful functional groups are tolerated and the synthetic utility of this method has been demonstrated through a series of transformations of the allene moiety. By applying this reaction as the key step, the total syntheses of naturally occurring allenic aromatic ethers, eucalyptene and terricollene A (first synthesis; 4.5 g gram scale), have been accomplished.